Field Static Loading Test on 40.8 m Span PCU Girder Bridge - Yusuf, Effendi; Aminullah, Akhmad; Irawati, Inggar Septhia (ASTONJADRO, 2025)
Field load testing using static loading is widely applied as a non-destructive testing (NDT) method for bridge assessment due to its practicality and ability to provide immediate, on-site results. This approach is suitable for both new and old bridges, requiring strength evaluation to understand the behavior and fundamental characteristics of the bridge. In this paper, 40.8 span PCU Girder Bridge was tested with a static loading test to obtain key performance and response indicators, such as the maximum deflection of the bridge under static load. The research findings showed that the bridge’s maximum deflection was -13.8 mm from the field load test, indicating the bridge structure is below the design limit of -35.7 mm, confirming its capacity to support a 192-ton load. The experimental results indicate that the bridge remains within the elastic range when subjected to the planned test loads. This suggests that the bridge has sufficient load-bearing capacity. Additionally, these findings reflect the current condition of the structure, which can serve as a foundation for ongoing structural health monitoring and future maintenance of the bridge.